Guest Recognition Control Accompanied by Stepwise Gate Closing and Opening of a Macrocyclic Metallohost. Issue 7 (18th November 2020) - Sakata, Yoko; Okada, Masahiro; Akine, Shigehisa
Abstract: Host–guest binding behavior of macrocyclic hosts is significantly influenced by the shapes and sizes of the hosts. In particular, closing/opening the apertures of the hosts controls the guest uptake/release. A post‐metalation modification method was used to achieve the open/close conversions. The starting open complex, [LCo2 (pip)4 ](OTf)2, was efficiently converted to the closed complex, [LCo2 (hda)2 ](OTf)2, which has a doubly bridged structure. The conversion of this closed complex to the open complex [LCo2 (hda)2 (OAc)] + was too slow to be completed, but this gate‐opening was dramatically accelerated by the addition of Na + . The Na + binding was also significantly enhanced by the gate‐opening, that is, conversion of [LCo2 (hda)2 ] 2+ to [LCo2 (hda)2 (OAc)] + . Abstract : When one door closes : The post‐metalation modification method is utilized for a two‐step conversion of a dicobalt(III) macrocyclic metallohost. The starting open complex, [LCo2 (pip)4 ] 2+, is efficiently converted to the closed complex, [LCo2 (hda)2 ] 2+, which is then converted to the open complex [LCo2 (hda)2 (OAc)] + . The gate‐opening in the second step is dramatically accelerated by the addition of Na +, and the Na + binding is also significantly enhanced by the gate‐opening.